The Role of Gamified Learning Media in Enhancing Students’ Motivation at State Madrasah Tsanawiyah - Dwi Novita (Sufiya Journal of Islamic Studies, 2024)
This study aims to examine the effect of using gamification-based learning media on student learning motivation at Madrasah Tsanawiyah Negeri 3 Simalungun. This research uses a quantitative approach. The sample amounted to 35 students who were purposively selected. Data were collected through a Likert scale questionnaire that had been tested with the help of SPSS, including validity, reliability, normality, homogeneity, T-test, F-test, and the coefficient of determination. The results showed that the use of gamification media has a significant influence on student learning motivation, with a coefficient of determination (R²) of 0.522. This means that 52.2% of learning motivation variables can be explained by the use of gamification media. This finding confirms that gamification is an effective learning strategy in increasing student engagement and motivation.